PENERAPAN ANALISIS INPUT-OUTPUT HIBRID UNTUK MENGUKUR PENGARUH AKTIVITAS SEKTOR-SEKTOR PEREKONOMIAN TERHADAP KUALITAS LINGKUNGAN KITA - Faried Wijaya Mansoer (Journal of Indonesian Economy and Business (JIEB), 1999)
Concern about the negative impact on environment promotes more attentionand policy to be directed toward efforts to implementation of sustainabledevelopment, in witch the process should be optimal and efficient. Various effortshave been tried to measure the environmental impact of economic sectors activities topursue such objective. This paper presents the application of l-O (Input-output)hybrid analysis by using Indonesia I-O Table. The result is a quantified impacts bysectoral, kind of energy/waste, and factor of origin namely domestic and import. Itmight be used as a base analysis for economic, energy-environment, and developmentpolicies.